Molecular Dynamics Research on Geometric Effect of Rectangular Groove Surface Morphology of Cu and Gr/Cu Substrates on Pesticide Molecule 2,4-D Adsorption - Zhang, Jingran (Langmuir : the ACS journal of surfaces and colloids, 2025)
Excessive pesticides can lead to environmental pollution and pose serious risks to human health. However, the adsorption mechanisms of the pesticide molecule 2,4-dichlorophenoxyacetic acid (2,4-D) on nanostructures, graphene surfaces, and systems combining nanostructures and graphene surfaces remain underexplored. Here, the influence of rectangular groove geometries on the adsorption of the pesticide molecule 2,4-D on Cu and graphene-coated Cu (Gr/Cu) substrates was investigated via molecular dynamics (MD) simulations. In particular, the effects of the geometric features (depth and width) on the equilibrium structure of the adsorption layer and the interactions between the substrates and the adsorbed molecules were investigated. First, the effects of varying geometric dimensions of rectangular grooves on the adsorption behavior of 2,4-D molecules were analyzed. At a groove width of 30 Å and depths of 3-12 Å, 2,4-D completely penetrated the groove bottom. Subsequently, the influence of the groove geometry on the graphene adsorption configurations on Cu substrates was evaluated. The graphene adsorption configurations on nanostructured rectangular groove surfaces with different depths and widths were classified into three types: full adhesion, partial adhesion, and suspension. Finally, the influence of rectangular grooves with varying widths and depths on the adsorption behavior of 2,4-D molecules on the Gr/Cu surface was examined. At a groove width of 30 Å and depths of up to 10 Å, increasing the groove depth facilitated the formation of the 2,4-D adsorption layer on the graphene surface. Conversely, at a groove depth of 5 Å and widths of within 20 Å, increasing the groove width promoted faster formation of the adsorption layer. Compared with the bare Cu substrate, the Gr/Cu substrate exhibited a significantly higher adsorption for 2,4-D molecules. These findings demonstrate that integrating graphene with rectangular groove structures on Cu not only promotes molecular diffusion but also improves the adsorption stability of 2,4-D molecules on the substrate surface